uSocial Realtime Berbasis Android Menggunakan Volley dan Algoritma BruteForce - Azizah Azizah; Fauziah Fauziah; Nur Hayati (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2020)
Communication can be done anywhere and anytime, making it easier for people to exchange information. Communicating today is very easy by utilizing various applications or media by using internet facilities such as Instagram, Facebook, WhatsApp Messenger, and others. The author builds an application that can connect users in communicating, exchanging information, and sharing the science that is the uSocial application. The app is created by applying the Firebase, Volley, and RecyclerView methods. These three methods are useful for running applications directly or In Real-time. Algorithm testing is done by comparing the Brute Force algorithm with the Horspool, and Knuth Morris Pratt algorithms. The results of Brute Force algorithm testing on word searches performed based on the length of search sentences resulting in 100% accuracy for 500 data trials as well as shortening the time for posts searches then better using Brute Force algorithms. The test results using the Whitebox method tested using three parameters, namely cyclomatic complex city, region, and independent path, produce 17. The program's flow and logic follow ANSI standards and there is no need to change the flow or plan back. At the same time, the results on the Blackbox testing of the functions in the application managed to produce the desired output.